TREATMENT OF LARGE AND GIANT MELANOCYTIC NEVI OF MAXILLOFACIAL AREA IN CHILDREN - A. S. Usol’Tseva; Yu. V. Stepanova; I. N. Krasnogorskiy; M. S. Tsyplakova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study determined the choice of treatment method according to morphological structure of large and giant congenital melanocytic nevi of maxillofacial region. MATERIALS AND METHODS. Several options of surgical treatment were applied in 40 children of different age such as local plasty, expander dermotension and transplantation of free skin graft. The features of maxillofacial region were taken into account. RESULTS. The scheme of staged surgical treatment was developed. All the patients had constant positive results. These data were evaluated conside ring choice of surgical treatment and features of morphological structure of removed nevi. CONCLUSIONS. The guidelines of staged surgical treatment developed by authors allowed them to improve the results of patient cure.